Modeling material behavior of AA5083 aluminum alloy sheet using biaxial tensile tests and its application in numerical simulation of deep drawing - Prakash, Ved; Kumar, D. Ravi; Horn, Alexander; Hagenah, Hinnerk; Merklein, Marion (International Journal of Advanced Manufacturing Technology, 2020)
Improvement in accuracy of the predicted results from numerical simulation results into a reduction of cost and time involved in tool design and experimental trials. However, the predicted results from finite element simulations are significantly affected by the chosen yield criterion and work hardening law. The selection of yield criterion and work hardening law depends on the characterization methods used for defining the material behavior. In this work, the mechanical behavior of AA5083-O aluminum alloy sheet is modeled by performing biaxial tensile tests using cruciform specimen and hydraulic bulging experiments in addition to uniaxial tensile tests. Biaxial to uniaxial yield stress ratios are determined using the equal plastic work principle from the flow curves obtained from these tests. The obtained ratios are used to find the coefficients of Yld2000-2d and Hill48 yield criteria which is then used in the numerical simulations of cylindrical cup deep drawing. Numerical simulations are also carried out using uniaxial and biaxial flow curves fitted with different isotropic hardening laws. Thickness distributions and the load-displacement curves are predicted and validated by performing cylindrical cup deep drawing experiments.
CRIS-Team Scopus Importer:2019-12-17
Keywords: Aluminum alloy; Cruciform specimen; Deep drawing; Finite element simulation; Hardening laws; Hydraulic bulge test; Yield criteria